2014
DOI: 10.1371/journal.pone.0101897
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Glomerular Filtration Rate in Pregnancy and Fetal Size

Abstract: BackgroundThe relationship of maternal glomerular filtration rate (GFR) in pregnancy to fetal size needs to be better characterized as it impacts an ongoing debate about confounding effect of maternal GFR in investigations of important environmental contaminants. We aimed to characterize the size of the association between maternal GFR and infant birth weight.Materials and MethodsA sub-cohort of 953 selected women (470 women with and 483 women without preeclampsia) in the Norwegian Mother and Child Cohort (MoB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 31 publications
2
46
2
1
Order By: Relevance
“…In fact earlier studies done in the 1970’s by Gibson et al showed that the lack of rise in GFR during early pregnancy is associated with women that have increased risks of unexplained stillbirths, abortions, or small for gestational age babies 43 . The same trends have been observed in more recent studies where there is a strong positive correlation between maternal GFR and fetal size 44 . Furthermore, the lack of rise in GFR during pregnancy can increase the levels of circulating uric acid during pregnancy and damage the glomerular filtration barrier, leading to an increase in proteinuria and glomerular damage 45 .…”
Section: Discussionsupporting
confidence: 87%
“…In fact earlier studies done in the 1970’s by Gibson et al showed that the lack of rise in GFR during early pregnancy is associated with women that have increased risks of unexplained stillbirths, abortions, or small for gestational age babies 43 . The same trends have been observed in more recent studies where there is a strong positive correlation between maternal GFR and fetal size 44 . Furthermore, the lack of rise in GFR during pregnancy can increase the levels of circulating uric acid during pregnancy and damage the glomerular filtration barrier, leading to an increase in proteinuria and glomerular damage 45 .…”
Section: Discussionsupporting
confidence: 87%
“…GFR describes the flow rate of filtered fluid through the kidney, and we postulate that higher GFR leads to more excretion of PFASs and thereby lower serum levels of PFASs. Because studies have indicated a possible association between GFR and infant birth weight [46], GFR might be considered a potential confounder in epidemiologic studies of PFASs and fetal growth. In fact, a recent study that examined the impact of GFR on associations between PFASs and birth weight, suggested that associations were largely attenuated due to confounding by GFR [47].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal glomerular filtration rate (GFR) was calculated for each woman in each pregnancy, based on the formula of Cockroft-Gault (GFR= (140–age) × weight(kg) × 0.85/(72 × serum creatinine (mg/dl)) (Morken et al, 2014). The average GFR of the two pregnancies was used in the models described below.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing maternal blood, cord blood, and breast milk samples studies have shown that PFASs can cross the placenta and partition into milk; hence pregnancy and breastfeeding are additional elimination pathways for women (Fromme et al, 2010; Glynn et al, 2012; Gutzkow et al, 2012). PFOS and PFOA levels are lower in pregnant women than non-pregnant women and the levels decrease across trimesters, suggesting that trans-placental transfer starts from early gestation; other physiological changes during pregnancy also contribute to this trend (Jain 2013; Javins et al, 2013; Morken et al, 2014). …”
Section: Introductionmentioning
confidence: 99%